3D printed continuous fibre reinforced composite corrugated structure. (15th January 2018) - Hou, Zhanghao; Tian, Xiaoyong; Zhang, Junkang; Li, Dichen
Abstract: A novel integrated manufacturing process based on continuous fibre reinforced thermoplastic composites 3D printing of continuous fibre reinforced composite lightweight structures (CFRCLSs) was proposed. Cross lap and panel-core lap design strategies were proposed to fabricate the CFRCLSs with a complex shape. The fracture modes during compression loading were analysed. Correlations between the process parameters, structure parameters, density, fibre content, and final performance of the printed specimens were discussed. The fibre content of the printed CFRCLSs were controlled by changing the process parameters. With a fibre content of 11.5% vol, a compression strength of 17.17 MPa was obtained for the 3D printed CFRCLSs. A heterogeneous lightweight sandwich structure specimen was fabricated to demonstrate process feasibility. This new and improved process has great potential for fabricating CFRCLSs with complex shapes, high mechanical properties, and multifunctional benefits.